Association between OPG polymorphisms and osteoporosis risk: An updated meta-analysis - Han, Xu; Zheng, Lai; Mu, Yi-Yang; Li, Hong-Zhuo; He, Xiao-Feng (Frontiers in Genetics, 2022)
Background: Numerous studies have demonstrated an association between osteoprotegerin (OPG) polymorphisms (A163G (rs3102735), T245G (rs3134069), T950C (rs2073617), G1181C (rs2073618)) and osteoporosis risk. However, their conclusions are inconsistent. In addition, some new studies have been updated, and more importantly, previous meta-analyses have not tested for false-positive results. In order to further explore these associations, we recently conducted a meta-analysis. Objectives: To study the relationship between OPG polymorphisms A163G, T245G, T950C, G1181C and the risk of osteoporosis. Methods: PubMed, Medline, International Statistical Institute (ISI), China National Knowledge Infrastructure (CNKI) and China Wanfang Database were used for research searches. Associations were assessed with five genetic models using odds ratios (ORs) with 95% confidence intervals (CIs). In addition, confidence in statistically significant associations was assessed using probability of false positive reports (FPRP), Bayesian probability of False discovery (BFDP), and Venice criteria. Results: On the whole, the OPG A163G polymorphism was not significantly associated with risk of osteoporosis. However, in a subgroup analysis, we found a significant association between OPG A163G polymorphism and susceptibility to osteoporosis in Caucasians. and the female. At the same time, the OPG G1181C polymorphism is associated with a significantly lower risk of osteoporosis . Moreover, a significantly decreased risk of osteoporosis was also discovered in Asian and the female. Finally, we did not find a close association between OPG T245 and T950C polymorphisms and osteoporosis risk. However, when we retained only studies in the control group that were consistent with Hardy-Weinberg equilibrium (HWE) and high-quality scores, we observed that the OPG A163G polymorphism increased the risk of osteoporosis in the overall analysis . Finally, after the credibility assessment, we concluded that all statistically significant association results in the meta-analysis in this study and those in the previous study were 'positive results with low confidence'. Conclusion: In conclusion, our study concluded that all meaningful results between OPG A163G, T245G, T950C, and G1181C polymorphisms and osteoporosis risk were false-positive results rather than true associations.